(untitled) (LEARNing Landscapes, 2015)
This paper draws on recent research on teacher collegiality and professional learning communities to unpack the nature, benefits and drawbacks of different forms of collegial relations, especially in circumstances of high stakes reform. In particular the paper examines the relative merits of pulling change by inspiring and enthusing teachers in their efforts by appeal to the moral principles of their work, or pushing change by placing teachers in situations requiring changes in practice in the hope that this will then lead to changes in their beliefs. The paper finds that teachers sometimes have to be drawn or pulled into professional learning communities, and sometimes they have to be driven or pushed by them. However, pulling should not be so weak that it permits no collaboration at all, and pushing should not be so excessive that it amounts to shoving or bullying. Instead, collaboration will often require the nudges of deliberate arrangements to enhance learning.